Hemiarthroplasty in the Hip Fracture Patient with Renal Impairment: To Cement or Not to Cement - Tan, Tong Leng (Hip Pelvis, 2019)
PURPOSE: Patients with chronic kidney disease (CKD) have a higher risk of complications when undergoing hip hemiarthroplasty. The primary aim is to test the null hypothesis that there is no difference between cemented and uncemented stem loosening rates in patients with CKD who receive a hip hemiarthroplasty for femoral neck fractures. The secondary aim is to determine the effect of increasing severity of renal disease on the rate of stem loosening in this CKD patient subset. MATERIALS AND METHODS: A retrospective study of all patients with CKD who underwent a hip hemiarthroplasty for a traumatic femoral-neck fracture between 2003 and 2013 was performed. Patients with a minimum of two-year follow-up were included; those with pathological fractures or loosening due to infection were excluded. The outcome measure was radiographic aseptic loosening of the stem, defined as progressive radiolucency of more than 2 mm, progressive subsidence or migration of the implant. RESULTS: One-hundred and nineteen cases were included in this study. Loosening occurred in 11 cases (9.24%). A comparison between cemented and uncemented groups revealed no difference in the rate of loosening (P=0.079). In all cases, worsening renal function did not increase the rate of loosening (P=0.311). The rate of loosening did not increase with worsening renal function in either the cemented (P=0.678) or uncemented groups (P=0.307). CONCLUSION: There is no difference in the rate of loosening between cemented and uncemented hemiarthroplasty for femoral neck fractures in the elderly with CKD. The rate of loosening did not increase with worsening renal function. All patients with renal impairment, not just those with end-stage renal failure, warrant close follow-up as early loosening can occur throughout the entire spectrum of renal disease.